2016
DOI: 10.1111/jcmm.12942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide deficiency on the pulmonary PTHrP system

Abstract: Nitric oxide (NO) deficiency is common in pulmonary diseases, but its effect on pulmonary remodelling is still controversial. As pulmonary parathyroid hormone‐related protein (PTHrP) expression is a key regulator of pulmonary fibrosis and development, the effect of chronic NO deficiency on the pulmonary PTHrP system and its relationship with oxidative stress was addressed. NO bioavailability in adult rats was reduced by systemic administration of L‐NAME via tap water. To clarify the role of NO synthase (NOS)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[1][2][3][4] Pulmonary vasoconstriction is induced by the reduction of vasodilators such as nitric oxide (NO) and/or the production of vasoconstrictors such as endothelin-1 and oxidative stress. [5][6][7][8] In addition, it is known that resistance to apoptosis mediated by bone morphogenic protein (BMP) signals or transforming growth factor (TGF)-β signals is involved in the excessive proliferation of pulmonary artery endothelial cells and smooth muscle cells. [9][10][11] However, the detailed mechanisms remain unclear.…”
mentioning
confidence: 99%
“…[1][2][3][4] Pulmonary vasoconstriction is induced by the reduction of vasodilators such as nitric oxide (NO) and/or the production of vasoconstrictors such as endothelin-1 and oxidative stress. [5][6][7][8] In addition, it is known that resistance to apoptosis mediated by bone morphogenic protein (BMP) signals or transforming growth factor (TGF)-β signals is involved in the excessive proliferation of pulmonary artery endothelial cells and smooth muscle cells. [9][10][11] However, the detailed mechanisms remain unclear.…”
mentioning
confidence: 99%
“…Former studies showed that lung structural remodelling after myocardial infarction can be attenuated by irbesartan, an angiotensin II receptor antagonist [12]. We have recently shown that captopril, an angiotensin converting enzyme inhibitor, can attenuate pulmonary induction of PTHrP, but not that of PTH-1 receptor, in a NO-deficiency model [1]. Collectively the data suggest that an infarct-dependent activation of the renin-angiotensin-system induces the expression of PTHrP and that this contributes to the formerly observed lung structural remodelling.…”
Section: Discussionmentioning
confidence: 98%
“…Our finding that elastin mRNA expression was not changed under conditions shown to increase pulmonary PTHrP mRNA expression is in fine agreement with the assumption that activation of the pulmonary PTHrP system attenuates transactivation of epithelial cells to myofibroblasts that favours pulmonary fibrosis. We have recently shown that the pulmonary expression of PTHrP is constitutively repressed by nitric oxide (NO) [1]. Inhibition of endothelial-derived NO formation significantly increased the expression of PTHrP, PTH-1 receptor, ADRP, and PPARγ.…”
Section: Discussionmentioning
confidence: 99%